Modernisation trends in public administration in Slovenia - Kukovič, Simona (Array, 2020)
The theory of public administration offers a wide range of paradigms or approaches that are developed as a consequence of various triggers from internal and external environment. The classical model of bureaucratic organization as outlined by Weber is no longer appropriate in modern countries, although it still remains the basis of public administration because of numerous transformations and upgrades. The first major reforms were introduced to public administration via the more modern and market-oriented New Public Management. However, Post-New Public Management approaches have recently developed as a reflection of social and political changes. In this paper, we offer an overview of modern approaches, which do not appear in pure form, but in the form of hybrids. There is no consensus, either in science or in practice, on the optimal direction of public administration development or on the preferential approach. This decision is left to the governments, bearing in mind that each public administration reform and hybridization of approaches affect the complexity of public administration. Analysing the reform of the Slovenian public administration, we have found that the current Strategy of Public Administration Development for 2015-2020 is based on modern elements and values of Post-New Public Management approaches and that reforms strive for modernization, but (as shown by the current crisis) a serious effort will be required in the future to achieve this goal.